ISO implementation effectiveness: Suppliers prospective - Abdul Raman, Abdul Aziz; Abdullah, E.C. (2007)
It has been five years since UM implemented ISO Quality Management System for all its process. However to date no systematic evaluation is done to quantify the effectiveness of the implementation for many processes. Purchasing supplies are one of the point emphasized in ISO 9001:2000 Quality Management System and it is covered under clause 7.4. In this paper the authors evaluate the effectiveness of implementing ISO clauses for purchasing equipments, chemicals, consumables and services. For this purpose eleven willing suppliers in Chemical Engineering Department was selected and given various questions with the intention of evaluating the effectiveness. Criteria such as tender information announcement, payment duration, simplicity of documentation, transparency and fairness are used to evaluate the effectiveness of the purchasing process. The suppliers were also asked to compare these criteria prior to ISO implementation in UM. Comparison is also made with Universities without ISO. From the feedback received it is very evident that from the suppliers perspective, the purchasing system has improved about 10-20% after the implementation of ISO system but there are plenty of room left for improvements. The results also show that the levels of satisfaction of the suppliers with non-ISO universities are about 5% less than UM.